2010
DOI: 10.1159/000301235
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 12: Epidemiology of Methicillin Resistant Staphylococcus Aureus Bacteraemia Amongst Patients Receiving Dialysis for Established Renal Failure in England in 2008: a joint report from the UK Renal Registry and the Health Protection Agency

Abstract: Background: From April 2007, all centres providing renal replacement therapy in England were asked to provide additional data on patients with Methicillin Resistant Staphylococcus aureus (MRSA) bacteraemia using a secure web based system established to capture data for the mandatory surveillance of MRSA bacteramia. Results: From April 2008 until March 2009 171 discrete episodes of MRSA bacteraemia were identified from the Health Protection Agency database as being potentially associated with patients in establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…The dataset included dialysis modality, type of dialysis access and use of non-tunnelled venous catheters within the preceding 28 days. The previous report confirmed that while dialysis patients remain at increased risk from MRSA there has been a continued year on year decline in the number of bacteraemias [3]. The report also provided the first experience of MSSA BSI reporting for the first six months of mandatory surveillance.…”
Section: Introductionmentioning
confidence: 58%
“…The dataset included dialysis modality, type of dialysis access and use of non-tunnelled venous catheters within the preceding 28 days. The previous report confirmed that while dialysis patients remain at increased risk from MRSA there has been a continued year on year decline in the number of bacteraemias [3]. The report also provided the first experience of MSSA BSI reporting for the first six months of mandatory surveillance.…”
Section: Introductionmentioning
confidence: 58%
“…It should be noted that although reporting is mandatory for these data collections (MRSA, MSSA and E. coli BSI and CDI), completion of documentation of information relating to renal failure is currently conducted on a voluntary basis depending on the data entry policy within the reporting NHS acute Trust. The methods used for the reporting of infections to Public Health England (PHE) have been described in previous UKRR reports (see appendix 1) [4,5].…”
Section: Methodsmentioning
confidence: 99%
“…The methods used have been described in previous registry reports (see appendix 1) [4,5]. Briefly, three stages of data collection and validation were undertaken by Public Health England (PHE):…”
Section: Methodsmentioning
confidence: 99%